Do bankers sacrifice value to build empires? Managerial incentives, industry consolidation, and financial performance - Joseph P. Hughes; William W. Lang; Loretta J. Mester; Choon-Geol Moon; Michael S. Pagano (Rutgers University, Department of Economics, 2001)
Bank consolidation is a global phenomenon. It may enhance the value of firms in the industry if, for example, it is driven by scale and scope economies, but skeptics often accuse bankers of sacrificing value to build empires. Using data on bank holding companies in the U.S., we find strong evidence of managerial entrenchment that influences how asset acquisitions and sales affect financial performance. We measure bank financial performance both by Tobin's q ratio and by its failure to achieve its highest potential market value, which we estimate using a stochastic frontier technique. We find evidence of entrenchment at banks with higher levels of managerial ownership, better growth opportunities, poorer financial performance, and smaller asset size. However, when managers are faced with better growth opportunities, they generally appear to have an elastic demand for agency goods (perquisites, shirking, risk avoidance, etc.). With regard to empire building, we find that an increase in asset size achieved by internal growth is associated with better performance at most banks, but an increase in acquired assets is associated with worse performance at banks with entrenched managers. In contrast, a larger amount of sold assets by banks with entrenched management is related to improved performance. We do not obtain this asymmetry between the effect of sales and acquisitions at banks not exhibiting entrenchment: larger sales and larger acquisitions both improve performance, a result predicted by Shleifer and Vishny (1989). Our evidence is consistent with the often cited role of scale economies as a driver of bank consolidation, but it also suggests that the benefits of asset acquisitions are not obtained by entrenched managers, who may be able to resist market discipline to build empires.
Keywords: G32; 330; consolidation; Fusion; Übernahme; Bank; Unternehmenserfolg; Tobin's Q; USA; Unternehmenswert